STUDYING THE CONDUCTIVITY OF POLYSTYRENE USING 2-(SUB.)-5- [3-(5-NITRO-FUR-2-YL)-PROPEN-2-YLDIENE]AMINO 1,3,4- THIDIAZOLES AS ADDITIVES BY MEASURING FORBIDDEN ENERGY GAP - Salih, Nadia; Yousif, Emad; Abdul Nabi, Mohammed; Hameed, Ayad; Salimon, Jumat (Al-Nahrain Journal of Science, 2018)
The optical properties of Polystyrene in the region from (200-900 m) were studied usingUV-VIS spectrophotometer by preparing composites with different organic materials. The opticaldata analyzed and interpreted in term of the theory of phonon assisted indirect electronic transition.It is observed that the energy gap of the samples, affected by the type of organic doping, andincrease the conductivity of the polystyrene